Penerapan Pendekatan Saintifik dalam Pembelajaran Biologi untuk Meningkatkan Minat Belajar Siswa SMA 8 Surabaya - Rozikin, Ahmad; Sanjaya, Edi (Journal of Science and Mathematics Education, 2025)
The decline in students' interest in learning Biology has become a recurring issue at the senior high school level, including at SMA Negeri 8 Surabaya. This study aims to analyze the implementation of the scientific approach in Biology instruction as an effort to enhance students' learning interest. The scientific approach emphasizes the processes of observing, questioning, experimenting, reasoning, and communicating, and is expected to create active, creative, and meaningful learning experiences. The research method used is classroom action research (CAR), conducted in two cycles. The research subjects were 11th-grade science students at SMA Negeri 8 Surabaya. Instruments used included observation sheets, learning interest questionnaires, and documentation of students' learning outcomes. The results showed that the implementation of the scientific approach significantly increased students' learning interest, as indicated by improved participation in discussions, persistence in completing assignments, and increased learning interest questionnaire scores from cycle I to cycle II. These findings suggest that the scientific approach is not only curriculum-relevant but also effective in creating a learning environment that fosters students’ emotional and intellectual engagement. Therefore, it is recommended that this approach be widely adopted in Biology instruction as well as in other subjects at the secondary education level.